PRACTICALITY OF DEVELOPING INTERACTIVE MULTIMEDIA BASED ON MACROMEDIA FLASH 8 ON LEARNING INTEGRATED THEMATIC ELEMENTARY SCHOOL - Arespi Junindra Arespi Junindra; Yalvema Miaz; Yeni Karneli; Elfia Sukma (Jurnal Cakrawala Pendas, 2023)
The implementation of learning objectives cannot be separated from certain aspects, one of which is the aspect of learning media, including interactive multimedia, which is very suitable for learning in the current technological era. However, the implementation in the field related to the use of interactive multimedia in learning has not been optimal, including the lack of optimal use of interactive multimedia based on computer applications, even though the facilities and infrastructure are adequate. This research aims to develop interactive multimedia based on Macromedia Flash 8 for integrated thematic learning in practical elementary schools. This type of research is R&D using the 4-D model consisting of four stages: define, design, develop, and disseminate. The subjects of this study were the fifth-grade students at SDN 32 Bungo Pasang, SDN 45 Bungo Pasang, and SDN 51 Bungo Pasang, Koto Tangah District, Padang City, totaling 62 students. The research data collection instrument was through practicality sheets, namely the educator's response questionnaire and the student's response questionnaire. The results showed that the practicality level of interactive multimedia was obtained with the teacher's response value of 95.56% in the "very practical" category and the student's response was 91.36% in the "very practical" category. Thus, the development of interactive multimedia based on Macromedia Flash 8 in elementary school integrated thematic learning is practically used in classroom learning. Terlaksananya tujuan pembelajaran tidak lepas dari aspek-aspek tertentu salah satunya ialah aspek media pembelajaran diantaranya multimedia interaktif yang sangat cocok diterapkan pada pembelajaran di era teknologi saat ini. Namun, pelaksanaan dilapangan terkait penggunaan multimedia interaktif dalam pembelajaran belum optimal diantaranya masih kurangnya pemanfaatan multimedia interaktif berbasis aplikasi komputer secara optimal padahal sarana dan prasarana memadai. Tujuan penelitian ini adalah mengembangkan multimedia interaktif berbasis macromedia flash 8 pada pembelajaran tematik terpadu sekolah dasar yang praktis. Jenis penelitian ini adalah R&D dengan menggunakan model 4-D terdiri atas empat tahap yaitu, define, design, develop, dan disseminate. Subjek Penelitian ini adalah peserta didik kelas V SDN 32 Bungo Pasang, SDN 45 Bungo Pasang dan SDN 51 Bungo Pasang Kecamatan Koto Tangah Kota Padang berjumlah 62 orang peserta didik. Instrumen pengumpulan data penelitian ini adalah melalui lembar praktikalitas yaitu angket respon pendidik dan angket respon peserta didik. Hasil penelitian menunjukkan bahwa, diperoleh hasil tingkat kepraktisan multimedia interaktif dengan nilai respon pendidik yaitu 95,56% pada kategori “sangat praktis” dan respon peserta didik yaitu 91,36% pada kategori “sangat praktis”. Dengan demikian, pengembangan multimedia interaktif berbasis macromedia flash 8 pada pembelajaran tematik terpadu sekolah dasar praktis digunakan dalam pembelajaran di kelas.